Distinct functional elements for outer-surface anti-interference and inner-wall ion gating of nanochannels. Issue 1 (December 2018) - Gao, Pengcheng; Ma, Qun; Ding, Defang; Wang, Dagui; Lou, Xiaoding; Zhai, Tianyou; Xia, Fan
Abstract Over the decades, widespread advances have been achieved on nanochannels, including nanochannel-based DNA sequencing, single-molecule detection, smart sensors, and energy transfer and storage. However, most interest has been focused on the contribution from the functional elements (FEs) at the inner wall (IW) of nanochannels, whereas little attention has been paid to the contribution from the FEs at the nanochannels' outer surface (OS). Herein, we achieve explicit partition of FEOS and FEIW based on accurate regional-modification of OS and IW. The FEIW are served for ionic gating, and the chosen FEOS (hydrophobic or charged) are served for blocking interference molecules into the nanochannels, decreasing the false signals for the ionic gating in complex environments. Furthermore, we define a composite factor, areas of a radar map, to evaluate the FEOS performance for blocking interference molecules. Nanochannels are often modified with functional elements, but most studies have focused on functionalizing only the inner wall. Here, the authors design nanochannels with distinct chemical modifications on the inner and outer surfaces, providing a route to dual-function channels.